Development of new organic electroactive materials for rechargeable batteries - Furtado, Olívia (2012)
The need for a clean and sustainable energy supply in the transportation sector have prompted electric vehicles as one of the options to reduce fossil fuel dependency and greenhouse gases emissions. Furthermore, electric vehicles are seen as enablers of the storage capacity of electric grids. In this context, the reasobnable energy density and cyclability reached by lithium-ion batteries based on inorganic cathodes have placed them in considerable advantage regarding energy conversation and storage [1, 2]. For higher energy density, lower cost and more environmentally acceptable batteries research efforts are presently focus on organic-based electrodes as a new approach to conventional inorganic cathodes. [3]. In his work, we carried out the development of a derivative of polymide (PI) for use as electrochemically active cathode material in rechargeable lithium batteries. Even though the application of polyimide as electrode material is scarcely found due to its insulating character, its aromatic imide group can be electrochemically oxidized and reduced in a reversible manner [4, 5]. This paper will present the studies on the synthesis and chemical characterization of a polyimide derivate and its evaluation as cathode organic polymer after electrochemical characterization. Test half-cell testing and battery constitution are being planned. The use of polyimide derivates is considered promising because of the potentiial increase in specific discharge capacity, not flammability, excellent thermal stability and high machanical strength. Furthermore since the polyimide is hydrolysable, its use can also be considered environmentally friendly.